Cooperation between parents and teachers. Sources of inspiration of contemporary synergy in the pedagogical thought of the polish enlightenment - Musiał, Ewa (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The problem of the relations of parents and teachers, mainly in the aspect of cooperation of these environments, has long been visible in Polish thought of pedagogy, has always been treated very seriously. In the age of the Enlightenment, in which the issue of education was of special importance due to its role in the process of leading the individual out of the world of myth and superstition to the liberating effulgence of reason. On the basis of the analyzed sources, it was shown that only effective cooperation of parents and teachers consisting in continuous complementing each other to guarantee the child as many experiments as possible necessary for its harmonious development. Ethical indications regarding the mutual relations of teachers and parents of students, characteristic ideas for the pedagogical thought of the PolishEnlightenment, and which may inspire contemporary activities to create optimal conditions for cooperation between parents and teachers.
Keywords: parents; teachers; pedagogical culture; pedagogization; cooperation